2019
DOI: 10.1002/er.4472
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer and cell performance of a unitized regenerative fuel cell with nonuniform depth channel in oxygen‐side flow field

Abstract: Summary In this study, the cell performance of nonuniform depth and conventional straight channel in a unitized regenerative fuel cell (URFC) is compared. Various shapes of oxygen‐side channel cases are also proposed. Several parameters, such as the distribution of reactants and products and current density and powers in fuel cell (FC) and electrolytic cell (EC) modes, are investigated. A steady‐state model of two‐dimensional, two‐phase, nonisothermal, and coupled electrochemical reaction is developed. Five ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This is because the reduction of the flow space leads to an increase in the pressure drop, which is similar to the phenomenon of occlusion. The pumping power in all cases can be described as: 19 P pumping = Δ pA in u in where Δ p (Pa) is the pressure drop from the inlet to the outlet, A in is the cross-section of the channel inlet, and u in is the average velocity at the anode inlet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the reduction of the flow space leads to an increase in the pressure drop, which is similar to the phenomenon of occlusion. The pumping power in all cases can be described as: 19 P pumping = Δ pA in u in where Δ p (Pa) is the pressure drop from the inlet to the outlet, A in is the cross-section of the channel inlet, and u in is the average velocity at the anode inlet.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was found that removing the shoulders between the channels and using metal foam as the flow distributor also improved the performance. 18 Song et al 19 designed a non-uniform depth channel in which the depth is narrowed along the flow direction, and found that narrowing the average channel depth can improve reactant transfer to the catalyst layer and avoid product blockage. Zhang et al 20 also found that decreasing the channel depth and increasing the width of the flow channel can enhance the transfer of water and heat in the electrolyzer, but too much width of the flow channel leads to an increase in the ohmic overvoltage.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Ohm's law, the charge conservation equation for electrons and protons can be expressed as 27 :…”
Section: Charge Transportmentioning
confidence: 99%
“…Where c i is the molar concentration of gas phase species i, S i is the source term of species i and it is related to the rate of electrochemical reaction in the CLs. D eff is the effective diffusion coefficient, and given by 22,27,34 :…”
Section: Transport Of Gas Phasementioning
confidence: 99%
See 1 more Smart Citation